Tachycardia induced cardiomyopathy due to ectopic atrial tachycardia originating from the atrial appendage: A case series and review of literature - Abhinav Aggarwal; Anil Yadav; Ankit Jain; Anunay Gupta (Indian Pacing and Electrophysiology Journal)
This case series describes four cases of tachycardia-induced cardiomyopathy due to incessant ectopic atrial tachycardias from the atrial appendage (three from the right atrial appendage, one from the left). P wave morphology changes on surface 12-lead electrocardiogram can be used to diagnose this relatively rare subset of tachycardias and localise the site of origin. Tachycardia induced cardiomyopathy is relatively more common in atrial tachycardias from the atrial appendage as compared to tachycardia from other sites1,2. Radiofrequency ablation is the treatment of choice and is associated with a high success rate. Oral ivabradine is another treatment option for cases where ablation is unsuccessful or if the patient is unwilling for ablation. For rare cases refractory to other treatment measures, surgical excision of the atrial appendage may be needed.